Hg 분위기 열처리에 따른 적외선 감지용 Hg0.7Cd0.3Te 박막의구조적 특성 변화 - 김광천; 이차헌; 최원철; 김현재; 김진상 (한국센서학회, 2010)
The liquid phase epitaxy(LPE) method was widely used to growth of mercury cadmium telluride(MCT) thin films. However, this method lead to Hg-vacancies in MCT thin film, because Hg has high vapor pressure at this temperature range. This is a well known defect in HgCdTe grown by LPE method. In this study, we report the development of techniques for improving the crystalline quality and controlling the composite uniformity of HgCdTe thin films using high- pressure Hg-ambient annealing method. As a result, we achieved the improvement of the composite uniformity of HgCdTe thin films. It was observed by the high angle annular dark field scanning TEM(HAADF-STEM) analysis. Moreover, new HgTe phase and a shrinking of lattice fringe were observed.